The Extended Self: Youth’s Identity in the Music Consumption of Indonesian Spotify Users - Khairunnisa Rahmasari; Mashita Phitaloka Fandia Purwaningtyas (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
The music streaming service provider app, Spotify, accommodates users to customize their music consumption to suit their needs. Not only for listening to music, but Spotify also allows users to show off their musical tastes through other social media channels. The process of music consumption in Spotify becomes a tool of identity construction as well as distinguishing individuals by their social circle, and makes individuals feel that they are part of a particular group. This study examined the process of constructing user’s identity through music consumption on Spotify, where there is a process of extended self into the social media sphere. This research was conducted with virtual ethnographic method towards Indonesian Spotify users. The results indicated that informants used music consumption in Spotify as a way to construct an extended self in the digital space, primarily through ownership of Spotify profiles and music preferences.